Economic evaluations of strategies to prevent sports and recreational injury among children and adolescents: a systematic review. Issue 4 (5th September 2018) - Michaels-Igbokwe, Christine; Lee, Raymond; Marshall, Deborah A; Currie, Gillian
Abstract : Objective: To identify, summarise and critically assess studies reporting costs and consequences of sport and recreation injury prevention strategies among children and adolescents. Design: Systematic review. Methods and data sources: We searched MEDLINE (Ovid), EMBASE, CINAHL, Pubmed, Econlit and SPORTDiscus and PEDE. Included studies were peer reviewed full economic evaluations or cost analyses of sport/recreation injury prevention among children and adolescents≤18 years of age. The Pediatric Quality Appraisal Questionnaire was used for quality assessment. Results: The initial search yielded 1896 unique records; eight studies met inclusion criteria. Six studies were related to injury prevention in the context of recreation, two were related to sports. For recreation studies in cycling and swimming: costs per head injury averted was US$3109 to $228 197; costs per hospitalisation avoided was US$3526 to 872 794; cost per life saved/death avoided was US$3531 to $103 518 154. Sport interventions in hockey and soccer were cost saving (fewer injuries and lower costs). Global quality assessments ranged from poor to good. Important limitations included short time horizons and intermediate outcome measures. Conclusions: Few rigorous economic evaluations related to sport and recreation injury prevention have been conducted. The range of estimates and variation in outcomes used preclude specific conclusions; however, where strategies both improve health and are cost saving, implementation should be prioritised. Future economic evaluations should incorporate time horizons sufficient to capture changes in long-term health and use utility-based outcome measures in order to capture individual preferences for changes in health states and facilitate comparison across intervention types.